Potassium fertilization of cauliflower and broccoli in a potassium-rich soil - Silva, Andre L. P. [UNESP]; Cecilio Filho, Artur B. [UNESP]; Mendoza-Cortez, Juan W. [UNESP]; Lima Junior, Joaquim A. (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2016)
Cauliflower and broccoli are important vegetables but have lacking and divergent information about potassium (K) fertilization in soil with a high K content. Two experiments were carried out from 2-1-2010 to 5-20-2010 in Jaboticabal City, Sao Paulo, Brazil, aiming to evaluate the effect of different K doses (0, 50, 100, 150 and 200 kg ha(-1) K2O, in potassium chloride) on the yield of cauliflower 'Verona' and broccoli 'BRO 68' in Rhodic Eutrudox soil with a high K content. The broccoli and cauliflower responded positively but differently to potassium fertilization. The maximum yield of broccoli (12,476 kg ha(-1)) was obtained with 160 kg ha(-1) K2O, while the yield of cauliflower increased linearly with increasing K dose, yielding 38,285 kg ha(-1) with 200 kg ha(-1) K2O.
Keywords: Brassica oleracea var. botrytis; Brassica oleracea var. italica; productivity